The lexical frequency of labial-velar stops in northern sub-Saharan Africa and its historical implications - (:unkn) unknown (My University, 2016)
Cross-linguistically, labial-velar stops (LVS) are rather rare, but they are known to be common in the languages of northern sub-Saharan Africa (NSSA). This paper presents the results of a large-scale survey of the lexical frequency of LVS in 336 languages of NSSA. Our primary findings are that (i) within NSSA, we can distinguish two major areas with high lexical frequency of LVS, (ii) LVS are significantly less common in so-called basic vocabulary and more common in the “expressive” parts of the lexicon. The paper also explores the possible implications of these findings with respect to the linguistic mechanisms and historical processes that have brought about the current distribution of LVS in NSSA.
Keywords: African Research